Strategi Pengembangan Usahatani Jamur Merang Di Desa Ciasem Tengah Kecamatan Ciasem Kabupaten Subang - fadillah, nurul nurul; Purnomo, Sulistyo Sidik; Wicaksana, Indrajit (Jurnal Ilmiah Wahana Pendidikan, 2025)
Straw mushroom cultivation is one of the agricultural sectors with the potential to contribute economically to farmers in Ciasem Tengah Village, Ciasem District, Subang Regency. Despite having a considerable market opportunity, this farming business still faces various challenges, such as limited capital, low access to technology, and competition from other regions. This study aims to analyze the internal and external factors affecting straw mushroom farming and formulate its development strategies. The method used is qualitative descriptive with purposive sampling techniques and SWOT analysis. The results show that internal strategic factors include strengths such as the existence of loyal customers, production facilities, and intensive management, as well as weaknesses such as limited capital, low human resources, and suboptimal harvest quality. External strategic factors consist of opportunities such as high market demand and the healthy consumption trend, as well as threats such as market competition and nhthe low interest of the younger generation in mushroom farming. Development strategies that can be implemented include improving production quality through farmer training, optimizing digital marketing to expand the market, and increasing access to information and technology to support more efficient farming. With the right strategies, straw mushroom farming in Ciasem Tengah Village is expected to develop optimally and contribute to improving farmers' welfare.